Peran Jaringan Sosial dalam Pembentukan Social Chemistry pada Penggunaan E-Commerce oleh Rumah BUMN Kepulauan Meranti Sebagai Sociopreneur Terhadap Optimalisasi Pemanfaatan Potensi Sagu - Yusmar Yusuf; Resdati Resdati; Rd Siti Sofro Sidiq; Achmad Hidir; Berkah Bahagiana (Postgraduate, University of Mataram, 2024)
The use of social networks in the formation of Social Chemistry by Rumah BUMN Pulau Meranti as a Sociopreneur is an innovation that allows optimizing the use of sago potential. This research aims to explore the role of social networks in supporting the success of Rumah BUMN Pulau Meranti in marketing sago products through E-Commerce. The research method used is a descriptive qualitative approach through interviews, observation and document analysis. The research results show that social networks play an important role in helping Rumah BUMN Pulau Meranti to expand market reach, increase awareness of sago products, and strengthen branding as a Sociopreneur. With good cooperation with various parties, Rumah BUMN Pulau Meranti can optimally utilize the potential of sago so that it has a positive impact on the local community and the surrounding environment. This research provides an important contribution to understanding the importance of the role of social networks in supporting the development of E-Commerce to increase the sustainable use of sago potential.